PERANCANGAN APLIKASI MULTIMEDIA PENGENALAN OBJEK WISATA DI KECAMATAN MORO BERBASIS ANDROID - haryani, r.fitri; Pangaribuan, Hotma (Computer Science and Industrial Engineering, 2023)
This article aims to implement the design of multimedia introduction to tourist attractions in Moro District based on android to the wider community. the steps in the multimedia application design process are problem identification, problem formulation, documentation research, data collection, application design and application results. The results of this study indicate that the design of multimedia applications for designing multimedia introduction to tourist objects in Moro District based on android, makes it easy for tourists to see tourist objects in Moro District with android-based smartphones. With this application, the management of tourist objects in Moro District is helped to introduce to foreigners who are not yet known that there are many attractions and uniqueness in the Moro Island area.